KEMAMPUAN BAKTERI Acetobacter xylinum MENGUBAH KARBOHIDRAT PADA LIMBAH PADI (BEKATUL) MENJADI SELLULOSA - Nadiyah Nadiyah; Krisdianto KKrisdianto; Aulia Ajizah (Universitas Lambung Mangkurat, 2005)
The capability of Acetobacter xylinum to convert carbohidrate of rice-bran to cellulose was studied. Six treatments: 0, 1, 5, 10, and 20 g/L of rice-bran water were applied, and the thickness, weight and fiber from cellulose as fermentation results were recorded. It was discovered that higher concentration of rice-bran increased the thickness, weight and amount of fibers. Significant increase in fiber were found among 1 g/L, 5 g/L, and 10g/L of rice-brand. Higher concentration of rice-brand did not produced significant increase in fibers.